“Writing from the Migration Experience”: On Narrative Strategies and Identity Patterns in the Texts of Polish (E)Migration Literature in Germany - Szymańska , Eliza (Porównania, 2022)
In the following article, several texts of Polish (e)migration literature in Germany are analysed in relation to the narrative strategies used by the authors and the patterns of identity presented in them. Narration is not perceived only as a lin- guistically-limited genre, but as a mode of organising individual and collective memory and determining one’s own identity. With the help of selected catego- ries (exoticisation, intercultural (double) mediation, alterisation, transcultural universalisation, transculturalisation), a wide range (of which particularism and universalism mark two ends) of possible ways of dealing with one’s own migrant status is presented. It is their autobiographical narration of identity that all the texts selected for the analysis have in common. The aim of this article is to show the different forms it can take.